CUBITAL TUNNEL SYNDROME: CURRENT DIAGNOSTIC AND TREATMENT STRATEGIES FROM SOCIOECONOMIC AND HEALTHCARE PERSPECTIVES — A NARRATIVE REVIEW - Budzik, Paweł; Kornatowska, Karolina; Wiekiera, Mateusz; Wiekiera, Adrianna; Kopciał, Szymon; Rataj, Jonatan; Jankowska, Justyna; Pysiewicz, Mateusz Michał; Marciszuk, Szymon (International Journal of Innovative Technologies in Social Science, 2026)
Background: Cubital tunnel syndrome (CuTS) is the second most common compressive neuropathy of the upper extremity, with an estimated prevalence of 1.8–5.9% in the general population. It represents a significant clinical and socio-economic problem, contributing to pain, functional impairment, and reduced work productivity. Aim: This narrative review aims to summarize current evidence on the pathophysiology, diagnostic approaches, and treatment strategies for CuTS, with particular emphasis on clinical outcomes and implications for healthcare systems. Methods: A narrative review was conducted using the PubMed database, including systematic reviews, meta-analyses, and clinical studies published between 2017 and 2026. Results: CuTS pathophysiology involves mechanical compression, traction, and ischemia of the ulnar nerve. Diagnosis is based on clinical examination supported by electrodiagnostic testing and ultrasound. Conservative treatment is effective in mild cases, while surgical techniques, including decompression and anterior transposition, show favorable outcomes. No single surgical method has demonstrated clear superiority. Treatment outcomes are influenced by disease severity and duration. From a healthcare perspective, delayed diagnosis is associated with increased costs and higher rates of surgical intervention. Conclusion: CuTS requires an individualized, evidence-based approach. Early diagnosis and optimized treatment strategies may improve clinical outcomes while reducing healthcare costs and socio-economic burden. Future approaches should focus on improving diagnostic pathways and access to cost-effective interventions.